Protein Factor Involved in Fatty Acid Desaturation of Linoleic Acid - Catalá, Ángel (1977)
It has been established that the enzyme system involved in stearyl-CoA desaturation reaction has three integral components of the microsomal membrane: the NADH-cytochrome b5 reductase, cytochrome b5 and the desaturase (Gaylor et al, 1970; Holloway et al, 1970; Holloway, 1971; Oshino et al, 1971, Shimakata et al, 1972). All these components have been separated and purified (Strittmatter et al, 1974; Enoch et al, 1976).